Evaluation of the incidence of congenital uterine anomalies in polycystic ovarian syndrome: tertiary center experience - Yavuz, Onur; Akdöner, Aslı; Mankan, Kadir Alper; Gündoğan, Kadircan; Okyay, Recep Emre; Doğan, Ömer Erbil (Frontiers in Medicine, 2025)
ObjectivesThe primary aim of the study was to compare the incidence of congenital uterine anomalies in polycystic ovarian syndrome (PCOS) patients with the control group.MethodsThis was a retrospective cohort study conducted at a tertiary center between January 2018 and January 2024. The study cohort included 297 patients, comprising 99 women with PCOS (PCOS group, 33.3%) and 198 healthy women whose partners had male factor infertility (control group, 66.7%). The uterine cavity was evaluated using hysterosalpingography (HSG) images according to the European Society of Human Reproduction and Embryology (ESHRE) and the European Society for Gynaecological Endoscopy (ESGE) consensus on the classification of female genital tract congenital anomalies and the American Society for Reproductive Medicine (ASRM) Müllerian anomalies classification guidelines. Demographic characteristics, physical examination findings, laboratory results, and HSG findings of the groups were compared. Analyses were performed with SPSS version 26.0. Variables that did not show a normal distribution were analyzed using the Mann–Whitney U-test. The chi-squared test and Fisher exact test were used to analyze categorical data. An inter-rater reliability analysis (Cohen’s kappa) was performed for HSG findings. The results were reported with a 95% confidence interval (CI). The p-value of <0.05 was considered statistically significant.ResultsOf the whole study cohort, 7.7% had congenital uterine anomalies (CUAs) according to the ASRM criteria and 4.7% had CUAs according to the ESHRE/ESGE classification. CUAs were 5.7 times higher in the PCOS group than in the control group according to the ASRM criteria and 5.5 times higher in the PCOS group than the control group according to the ESHRE/ESGE classification system (17.2% vs. 3%, p < 0.0001; 10.1% vs. 2%, p = 0.003, respectively). Partial septate uterus (ASRM and ESHRE/ESGE classifications) was the most frequently detected CUA in the PCOS group (9.1% vs. 1.5%, p = 0.003). According to the ASRM classification, the partial septate uterus was followed by the arcuate uterus. It was 4.7 times more common in the PCOS group (7.1% vs. 1.5%, p = 0.01).ConclusionWe found that the frequency of CUA was higher among PCOS patients. Prospective studies are needed to examine anti-Müllerian hormone (AMH), serum sex steroids, and pregnancy complications in more detail to clarify pathophysiology and clinical implications.